Robotic‐assisted laparoscopic prostatectomy: An update on functional and oncologic outcomes, techniques, and advancements in technology. Issue 7 (15th September 2015) - Ramirez, Daniel; Zargar, Homayoun; Caputo, Peter; Kaouk, Jihad H.
Abstract : The robotic platform has revolutionized the management of prostate cancer over the last 15 years. Several techniques have been developed to improve functional and oncologic outcomes, including meticulous apical and posterior dissection, nerve sparing techniques, bladder neck and urethral length sparing, and anastomotic reconstruction. Future developments involving novel single‐site, robotic technology will undoubtedly further the field of minimally invasive urology. These topics are reviewed within this article. J. Surg. Oncol. 2015;112:746–752 . © 2015 Wiley Periodicals, Inc.